Snakebites in Jordan: A clinical and epidemiological study. (March 2022) - Abu Baker, Mohammad A.; Al-Saraireh, Mohammad; Amr, Zuhair; Amr, Samir S.; Warrell, David A.
Abstract: The epidemiology features and clinical symptoms associated with 121 cases of snakebite requiring admission to 24 hospitals in Jordan, during 2018–2020, are discussed. Ninety-six of them (79%) brought with them to the hospital the snake that bit them or a photograph of it. Echis coloratus was responsible for 68 of the bites and 6 fatalities. Sex ratio was 3.2 males: 1 female, with an overall average age of 27 ± 14.36 years. The highest incidence of bites was reported in September. Bites were most common on hands and legs. The period of hospitalization ranged from 1 to 36 days. Irbid and Karak governorates had the highest number of snakebites, most cases being reported from agricultural areas and among farmers. Clinical symptoms associated with five species of venomous snakes are described along with illustrative case histories. Symptoms associated with Echis coloratus bites included local swelling and necrosis, coagulopathy and bleeding, microangiopathic hemolytic anemia, thrombocytopenia, and acute kidney injury (AKI) and chronic renal failure. Daboia palaestinae victims exhibited ecchymoses, local swelling and necrosis, with one case of angioedema. Other symptoms included thrombocytopenia, coagulopathy, microangiopathic hemolysis and local and systemic bleeding, as well as AKI. A single case of envenoming by Macrovipera lebetinus developed the following symptoms; swelling, severe pain, extensive ecchymoses, neutrophil leukocytosis, normochromic normocytic anemia and aggregated platelets with thrombocytopenia. Symptoms associated with two cases of Pseudocerastes fieldi included swelling that spread from bitten hands, and mild abnormalities of platelet count and bleeding time. Four cases of envenoming by Atractaspis engaddensis exhibited severe pain, local swelling, erythema, numbness and tissue necrosis. One of them developed acute systemic symptoms. The only antivenom currently available in Jordan, is VINS "Snake venom antitoxin (Biosnake)", manufactured in India using venoms of three African snakes that do not occur in Jordan. It proved clinically ineffective against envenoming by Jordanian Viperidae, failing to correct coagulopathy and life-threatening hemorrhage, and to prevent AKI. Highlights: This study is intended to serve public health providers in Jordan concerning snake bites. The epidemiology and clinical symptoms associated with snake bites and current treatments with antivenoms is discussed. Antivenoms used Jordan is not effective based on clinical outcomes.